2017
DOI: 10.5603/fm.a2016.0079
|View full text |Cite
|
Sign up to set email alerts
|

Diastema size and type of upper lip midline frenulum attachment

Abstract: Patients with diastema have more often oversized upper lip frenulum attachment then patients without diastema. The most often type of frenulum in patients with diastema is papillary and papilla penetrating type. Type of upper lip frenulum attachment has an impact to the size of diastema.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 26 publications
2
14
0
1
Order By: Relevance
“…19,23 If the continuous band of maxillary labial frenum crosses in between the two maxillary central incisors, it causes midline diastema and is also reported to affect the growth of premaxillary region. 1,24,25 In this instance, the papillary and papillary penetrating frenum attachment are the only two considered as pathological. 15 In this study, very less number of the papillary type (6.2%) and papillary penetrating type (4.1%)…”
Section: Discussionmentioning
confidence: 99%
“…19,23 If the continuous band of maxillary labial frenum crosses in between the two maxillary central incisors, it causes midline diastema and is also reported to affect the growth of premaxillary region. 1,24,25 In this instance, the papillary and papillary penetrating frenum attachment are the only two considered as pathological. 15 In this study, very less number of the papillary type (6.2%) and papillary penetrating type (4.1%)…”
Section: Discussionmentioning
confidence: 99%
“…The results of the study of Laohapensang and Díaz-Pizán, similar to our present study, did not show any significant difference in sex with the prevalence of frenum. 18,19 Among the 639 children examined, 214 (33.5%) had high frenum and 425 (66.5%) had normal frenum, and the results showed that there was a significant relationship between high frenum and median diastema (p value = 0.014).…”
Section: Discussionmentioning
confidence: 98%
“…In these age ranges, gingival insertion was more prevalent in the former and mucosal insertion was more prevalent in the latter. They established there is a relationship between age and type of insertion since the growth and development of both the maxilla and the teeth cause the frenulum to undergo a migration in coronal-apical direction (14). This migration becomes stronger between 11 and 16 years due to the growth trend in the coronal direction of the alveolar ridge (15).…”
Section: Discussionmentioning
confidence: 99%